Initial Experience with Novel Single-Use Disposable Ureteroscopy: A Prospective, Single Arm 90-Day Trial of the Axis Ureteroscope. Issue 2 (4th March 2021) - Large, Tim; Rivera, Marcelino; Nottingham, Charles; Agarwal, Deepak; Mellon, Matthew; Krambeck, Amy
Abstract: Introduction: Novel digital disposable ureteroscopes are becoming more commonplace in endourological practices. We trialed the Axis™ single-use ureteroscope, which is distributed within the United States by Dornier MedTech. Our goal was to demonstrate clinical equivalence to our reusable platform and to evaluate the cost-effectiveness of a single-use digital ureteroscope. Methods: We conducted a prospective 90-day trial where all flexible ureteroscopic procedures were completed using the single-use ureteroscope. The cases were monitored for scope failure, scope deficiencies and surgeon satisfaction scores via an immediate postoperative REDCap® survey. We also performed a cost analysis between reusable scopes and the single-use ureteroscope. The cost of the reusable platform included the amortized initial purchase, maintenance and clean processing. Results: Over a 90-day period, we performed 93 flexible ureteroscopy procedures with a single-use ureteroscope, of which 74 were completed using Axis. After controlling for operating room time and disposable items used, the utilization of Axis was associated with an average reduction of $140.31 per case. Extrapolating the per-case savings over an annual case volume, we estimate a total savings of $56, 127.15. There were no disposable scope malfunctions. There were 4 (4.3%) cases converted to reusable scopes due to image quality (1), inadequate secondary deflection (2) and a tight ureter (1). Mean±SD score for image quality, mobility and ergonomics was 9.1±1.1, 8.9±1.1, 9.3±1.1, respectively. The 90-day complication rates were equal to our controls. Conclusions: We demonstrated that the Axis single-use digital ureteroscope is equivalent in function to our digital reusable scope and reduced the cost of flexible ureteroscopy.